Managing hazards, reducing risks and increasing investments in agriculture -some perspectives : critical analysis of policy issues for repositioning agriculture in the Caribbean - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
This special paper seeks to widen understanding and promote a new mindset with respect to three issues critical to the agriculture development process: 1) Natural hazards and disaster mangement in agriculture in the Caribbean; 2) Multi-commodity agricultural insurance for risk reduction, and 3) Catalysing and expanding investments in agriculture and rural areas.